A Few Remarks on the Study of Deities - Nakata, Ichiro
A Review Article on J. J. M. Roberts, The Earliest Semitic Pantheon: A Study of the Semitic Deities Attested in Mesopotamia before Ur III, the Johns Hopkins University Press, Baltimore and London, 1972, xvii, 174 pp.